Idiolekt Bolesława Prusa. Przegląd najnowszych ustaleń - Czachorowska, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
This article is intended to approximate arrangements for features characteristic writing of Prus, from the publication of monographs, which appeared in the last decade, after 2006, because they are not as well known as the earlier comments on writer’s idolect placed even in studies Bystroń or Bachórz. Notes on writing of Prus has been divided into several thematic areas: vocabulary topography (depicting the formation of landscape, the author’s preferred method of constructing space and filling it with specific object), color names (the world of colours, which enabled the writer to expose an entire palette of colour and shade names), floral vocabulary, used by the writer, war and military (this article contains an overview of the functions of military language within nomina militaria in the works of Bolesław Prus for example) and trade vocabulary.